WHY ETHNOGRAPHY MATTERS: On Anthropology and Its Publics - FASSIN, DIDIER (Cultural anthropology, 2013)
Based on the experience of researching and writing a book on urban policing in France and its reception by the media and various audiences, this essay discusses the challenges facing a public ethnography—distinguished from public sociology or anthropology. First, I differentiate two tash (popularizing and politicizing) and multiple publics (imagined or encountered). Second, I plead for the exploration of understudied objects and terrains (black holes) and the attention to the ordinary as a way to transform the perspective on the world (critical potentialities). Third, I evoke the risks related to the appropriation of the work by the media (popular translation) and the loyalties toward the diverse and sometimes opposed subjects of the research (public debt). My conclusion underlines why rendering public the worh of critical ethnography matters for contemporary societies.